Geometry and Segmentation of Cerberus Fossae, Mars: Implications for Marsquake Properties. Issue 1 (23rd January 2022) - Perrin, C.; Jacob, A.; Lucas, A.; Myhill, R.; Hauber, E.; Batov, A.; Gudkova, T.; Rodriguez, S.; Lognonné, P.; Stevanović, J.; Drilleau, M.; Fuji, N.
Abstract: The NASA InSight mission to Mars successfully landed on 26 November 2018 in Elysium Planitia. It aims to characterize the seismic activity and aid in the understanding of the internal structure of Mars. We focus on the Cerberus Fossae region, a giant fracture network ∼1, 200 km long situated east of the InSight landing site where M ∼3 marsquakes were detected during the past 2 years. It is formed of five main fossae located on the southeast of the Elysium Mons volcanic rise. We perform a detailed mapping of the entire system based on high‐resolution satellite images and Digital Elevation Models. The refined cartography reveals a range of morphologies associated with dike activity at depth. Width and throw measurements of the fossae are linearly correlated, suggesting a possible tectonic control on the shapes of the fossae. Widths and throws decrease toward the east, indicating the long‐term direction of propagation of the dike‐induced graben system. They also give insights into the geometry at depth and how the possible faults and fractures are rooted in the crust. The exceptional preservation of the fossae allows us to detect up to four scales of segmentation, each formed by a similar number of 3–4 segments/subsegments. This generic distribution is comparable to continental faults and fractures on Earth. We anticipate higher stress and potential marsquakes within intersegment zones and at graben tips. Plain Language Summary: The landing of the InSight mission on Mars and the deployment of its seismometer have renewed the interest of active Martian structures that could trigger seismic events. In this study, we focus on one of these structures, Cerberus Fossae, which is a large fracture network situated close to the landing site. We perform a detailed mapping of the fossae based on high‐resolution satellite images and present an analysis of their lateral segmentation and morphology. We assess an eastward direction of long‐term propagation of the fossae. We also find that the fossae are laterally segmented at four different scales: fossae are divided into major segments, which are themselves divided into secondary segments and so on. At each scale of segmentation, a similar number of three to four subsegments is found. This number is also observed along terrestrial fault systems. These results allow us to assess the overall and local stress concentrations along the fossae: we infer that those stresses are higher eastward near the tip of the fossae and at intersegment zones. Since marsquakes are difficult to locate precisely with a single seismic station, our study is an asset to reduce uncertainties and to better understand the source properties. Key Points: Width and throw at Cerberus Fossae decrease from west to east, indicating the direction of long‐term propagation of the dike‐induced grabens Cerberus Fossae are laterally divided into a similar number of major segments and sub‐segments, as observed along terrestrial fault systems Understanding the long‐term propagation and segmentation of Cerberus Fossae helps to delineate marsquake locations during the InSight mission